Enterohepatic Helicobacter species – clinical importance, host range, and zoonotic potential. (2nd November 2021) - Ochoa, Sofia; Collado, Luis
Abstract: The genus Helicobacter defined just over 30 years ago, is a highly diverse and fast-growing group of bacteria that are able to persistently colonize a wide range of animals. The members of this genus are subdivided into two groups with different ecological niches, associated pathologies, and phylogenetic relationships: the gastric Helicobacter (GH) and the enterohepatic Helicobacter (EHH) species. Although GH have been mostly studied, EHH species have become increasingly important as emerging human pathogens and potential zoonotic agents in the last years. This group of bacteria has been associated with the development of several diseases in humans from acute pathologies like gastroenteritis to chronic pathologies that include inflammatory bowel disease, and liver and gallbladder diseases. However, their reservoirs, as well as their routes of transmission, have not been well established yet. Therefore, this review summarizes the current knowledge of taxonomy, epidemiology, and clinical role of the EHH group.